The Abstract Police: A conceptual exploration of unintended changes of police organisations. (December 2019) - Terpstra, Jan; Fyfe, Nicholas R; Salet, Renze
As a consequence of the 2013 police reforms in the Netherlands and Scotland, the police in both countries have made a shift towards a fundamentally different kind of organisation: the Abstract Police. The increasing abstract character resulted in changes in the internal and external relations of the police. The police became more formalised and dependent on rigid systems and system information. Citizens and communities became more at a distance. Gradual and long-term processes may have similar consequences. For that reason it may be expected that the increasingly abstract character of the police may also be found elsewhere.